The Moderating Effect of Financial Literacy on the Determining Influence of Firm Value Factors - Ahmad, Yusuf Falaqi; Guntur Kusuma Wardana (I-Finance Journal, 2024)
The goal is to ensure the company's continuous growth and smooth operation, thereby benefiting the financial well-being of issuers or shareholders. The purpose of this research is to identify the moderating influence of financial literacy on the company's value and the relative importance of profitability, investment decisions, and dividend policies. The population in this study consists of 186 members of the IFSB. Sample selection was done using purposive sampling techniques, resulting in 11 Sharia banks in the Asian region as samples. The data used are secondary data taken by accessing the annual financial reports of each Sharia bank on its official website for the period 2019–2022. By utilizing multiple regression model analysis tools on panel data and carrying out interaction tests, which are generally known as moderated regression analysis using Eviews 10. The findings indicate that, partially, investment decisions and profitability significantly influence the company's value, but dividend policies do not play a significant role in affecting the company's value. Financial literacy is proven to moderate the impact of profitability and investment decisions on the company's value but cannot moderate the impact of dividend policies on the company's value. In conclusion, profitability and investment decisions significantly contribute to the increase in the company's value and can be strengthened by financial literacy, while the increase in dividend policies actually decreases the company's value.